Comprehensive characterization and environmental implications of industrial and hazardous incineration ashes: insights into chemistry, mineralogy, elements’ fractionation and leaching potential - Monika Kasina; Anna Telk; Małgorzata Wendorff-Belon (Scientific Reports, 2024)
Abstract Global economic growth and population expansion contribute to heightened solid waste production, creating environmental challenges. Sustainable waste management, notably incineration, is crucial for volume reduction, energy recovery, and resource utilization. The escalating reliance on waste incineration underlines the critical necessity for detailed waste characterization. Our study focuses on industrial and hazardous incineration residues (IHWA) and provides essential insights into their mineral and chemical composition employing various analytical techniques, including sieve analyses, laser diffraction, X-ray powder diffraction, FT-IR spectroscopy, SEM-EDS, and leaching behavior, thus contributing to filling a gap in the current knowledge. The majority of IHWA particles (41%) were smaller than 500 μm, with a significant portion (34%) in the 200–400 μm range, which increases their leaching potential. Toxic elements, including Cr, Cu, and Zn, were detected at elevated levels, with Zn concentrations exceeding EU soil limits by over 250 times, what underscore environmental risks and demand proper waste treatment. The complexity of mineral composition and bonds within the sample indicates the necessity for a thorough environmental assessment to understand the potential impacts on the ecosystem. Sequential extraction revealed that Zn (90.32%), Cd (64.22%), and Hg were predominantly found in the mobile fractions, indicating a high potential for leaching and environmental hazards. In contrast, elements like Cu, Cr, and Pb were primarily associated with immobile fractions. Mineral phases such as calcite and halite dissolved during the first extraction step, while other crystalline phases, including quartz and magnetite, remained stable throughout the process. The stability of other mineral phases in all results and the low leaching potential of elements in IHWA indicate that some mineral phases could suppress the leaching efficiency of elements.